Efektivitas Psikodrama untuk Menurunkan Tingkat Depresi dan Meningkatkan Self-Esteem pada Penderita Depresi - Anggoro, Luke Setyo (Fakultas Psikologi Universitas Sanata Dharma, 2025)
The aim of this research is to determine the effectiveness of Psychodrama in reducing levels of depression and increasing self-esteem in individuals who experience depressive disorders. The pre-experimental one group pretest-posttest method was used as the research design. The sampling technique uses purposive sampling. A total of 10 people with an age range of 21-55 years were used as research participants. The instruments used are the Indonesian version of BDI II for depression and the Indonesian version of RSES to measure self-esteem, these measuring instruments have been tested for validity and reliability. Therapeutic techniques use psychodrama. Data analysis technique using paired sample t test. The results obtained from the research were that the level of depression decreased significantly. This is based on the t test with a p value which obtained a value of 0.000 0.005. Then there is also a significant difference in self-esteem, as proven by the t test analysis with a p value which obtained a value of 0.000 0.005. According to statistical data analysis, it can be concluded that psychodrama can reduce levels of depression and increase self-esteem in individuals who experience depressive disorders.